An investigation into the best management practices for mountain bike parks and trail centres threatened by tree pests or pathogens - Martin, Thomas Isaac (2025)
After the closure of two major UK bike parks, Aston Hill in the Chilterns and Revolution in North Wales, due to outbreaks of Ash Dieback and Phytophthora Ramorum, an investigation was carried out investigate the management approaches taken at each location. Additionally, this study presents findings about the scale of UK mountain biking, distribution of trails plus wider environmental issues associated such as wild/off-piste trails and social conflicts. Mountain biking is a fast-growing recreational activity that frequently takes place in forested landscapes. In the UK, these woodland environments are increasingly threatened by pests, pathogens, and conflicting land-use pressures, raising questions about access, sustainability, and trail management. A mixed-methods approach was employed, combining GIS land cover analysis, Strava heatmap data, action camera video content, online surveys, and semi-structured interviews with bike park owners and land managers. As well as Aston Hill and Revolution, two further case studies were investigated in detail, Hemlock Stone in Nottingham, and Wharncliffe Woods near Sheffield. This enabled the original case studies to be contrasted with more informal locations to see how management approaches may differ. It was determined that the extensive felling work completed at both sites was the best decision despite the various environmental and social impacts. However, it was also established that there is scope for improvement in the management of recreational spaces, especially in terms of public education and communication.